Criminological Contributions for the Comprehension of Transnational Corruption - Olasolo, Héctor (2023)
This article studies different criminological perspectives that help to fathom the phenomenon of transnational corruption. To this end, we will first study the characteristics of contemporary societies from different criminological viewpoints and then explain how these contribute to the study and comprehension of transnational corruption. In addition, multiple criminological perspectives will be analyzed, such as white-collar and mass media criminology, victimology, green and maldevelopment criminology, crimes of globalization and macrocriminality, among others.